Analysis of the mental health of pharmacy students at A number of public and private universities in Indonesia - Nurul Amalia Fadilah; Habibie Habibie; Susi Ari Kristina; Dyah Aryani Perwitasari; Najmiatul Fitria; Rusli Rusli; Muh. Syahruddin; Bustanul Arifin (Elsevier, 2024)
Background: This study examines the mental health of pharmacy students at various state and private universities in Indonesia, as well as the factors that influence it. The low mental health of pharmacy students can be found in a third of some countries. Similar findings occurred in the United States, France, and several Asian countries. However, there has been no research involving various universities in Indonesia to identify the factors that influence their mental health. Methods: This research used a cross-sectional method involving students from western, central, and eastern Indonesia. It used the DASS-21 (Depressin Anxiety and Stress Scale) and BRS (Brief Resilience Scale) instruments. Results: The results of the DASS-21 analysis of pharmacy students in Indonesia, the majority reported experiencing normal depression with a score of 3.198, normal anxiety with a score of 1.858, and stress with a score of 3.621. Mental resilience with the BRS instrument: 18 % of state university students reported medium-low, while private university students reported 17.5 % (p < 0.012). Influencing factors vary between public and private universities. Academic pressure is a major trigger, with students tending to seek support from their close friends. These findings provide an in-depth understanding of pharmacy students' mental health conditions in Indonesia, as well as strategies to overcome this problem, such as creating special spaces for mental health-related counselling at both types of universities. Conclusion: This study confirms the normal prevalence of mental health problems among pharmacy students in Indonesia, especially depression and low mental resilience. The study showed the relationship between depression, anxiety, stress, and mental resilience, indicating that the severity of a mental problem correlates with a decrease in mental resilience. A special room is required for health counselling.